2021
DOI: 10.1089/dia.2020.0471
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Improvement Using Continuous Glucose Monitoring by Baseline Time in Range: Subgroup Analyses from the DIAMOND Type 1 Diabetes Study

Abstract: The DIAMOND study demonstrated that real-time continuous glucose monitors (rtCGMs) improve glycemia for adults with type 1 diabetes using multiple daily injections. This analysis explores the relationship between baseline time in range (TIR) and improvement in TIR using rtCGMs or self-monitoring of blood glucose (SMBG). Baseline TIR was divided into three categories: <40% (9.6 h per day), <50% (12 h per day), and <60% (14.4 h per day). Compared with SMBG, use of rtCGMs increased mean TIR by an additional 16 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“… 16 Similar findings were observed among participants with lower baseline TIR. 17 Our results are consistent with and expand these findings to patients with type 2 diabetes on less intensive insulin therapy. The marked reduction in time spent with glucose >250 mg/dL in the subgroup with baseline HbA1c values ≥10% was achieved without significant differences in diabetes medication changes between groups, including the initiation of prandial insulin.…”
Section: Discussionsupporting
confidence: 90%
“… 16 Similar findings were observed among participants with lower baseline TIR. 17 Our results are consistent with and expand these findings to patients with type 2 diabetes on less intensive insulin therapy. The marked reduction in time spent with glucose >250 mg/dL in the subgroup with baseline HbA1c values ≥10% was achieved without significant differences in diabetes medication changes between groups, including the initiation of prandial insulin.…”
Section: Discussionsupporting
confidence: 90%
“…A one-sample t-test was used to describe GV in type 3c diabetes mellitus as compared to standard ranges described in the ATTD consensus. 12 Group differences in GV were also evaluated using one-way ANOVA model, with further post hoc testing performed to determine the association. An independent t-test was used to compare differences in GV in type 3c diabetes mellitus participants who either had or did not have pancreatic enzyme supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Randomised control trials have shown improved glycaemic control in both people with type 1 diabetes mellitus and type 2 diabetes mellitus with higher initial HbA 1c using CGM compared to self‐monitoring blood glucose methods 12–15 . There is also strong evidence for the use of CGM in type 1 diabetes mellitus with hypoglycaemia unawareness or frequent hypoglycaemic events, including nocturnal hypoglycaemia 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycemic control is a crucial aspect of the management of diabetes mellitus (DM) and is essential for the prevention of complications in both human and veterinary medicine. Continuous glucose monitoring systems (CGMSs) are frequently used in humans with diabetes, and clinical studies have shown they are effective in reducing hypoglycemia and improving glycemic control [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Thanks to their high performance, CGMSs have gained popularity among veterinarians and are increasingly being used in diabetic dogs (DD) and cats [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%